Pulmonary Langerhans cell histiocytosis—an unlikely diagnosis in a nonsmoker with clubbing and concomitant celiac disease: a case report - Swaroop Kumar Mudda; Dhruv Bansal; Priya Bansal; Ritika Sud; Motilal Negi (The Journal of Association of Chest Physicians)
Pulmonary Langerhans cell histiocytosis (PLCH) is a disease characterized by the infiltration of Langerhans cells into the lungs, affecting young adults with a history of smoking. Spontaneous pneumothorax is a recognized complication of PLCH. We present a case of a 19-year-old male nonsmoker who presented with recurrent pneumothorax, two episodes within a period of one month. Diagnostic workup, including imaging studies and lung biopsy, confirmed the diagnosis of PLCH. This case highlights the importance of considering PLCH in cases of recurrent pneumothorax, even with no history of smoking, and emphasizes the importance of timely diagnosis and management to prevent long-term pulmonary complications.